Cognitive self change : how offenders experience the world and what we can do about it - Bush, Jack, 1938-; Harris, Daryl, 1968-; Parker, Richard, 1959- (Chichester, West Sussex : John Wiley & Sons, Ltd, 2016)
"This book draws on the latest literature to highlight a fundamental challenge in offender rehabilitation; it questions the ability of contemporary approaches to address this challenge, and proposes an alternative strategy of criminal justice that integrates control, opportunity, and autonomy"--
Includes bibliographical references and index.
Introduction: Understanding Offending Behaviour Hard-Core Cognitive Self Change A human connection Phenomenology and self-reports: some preliminary comments about method Chapter Summary 1. The Idea of Criminal Thinking The Idea of Criminal Thinking Ellis, Beck, and Antisocial Schemas Psychopathology or irresponsibility An alternative point of view 2. Offenders Speak Their Minds Three young women Three Violent Mental Health Patients Two problematic groups Three British gang members Conclusions and Interpretations 3. Cognitive-Emotional-Motivational Structure Will and Volition, Self and Self-interest The Model Basic Outlaw Logic: learning the rewards of criminal thinking Variations of Criminal Thinking Conclusions and Implications 4. Supportive Authority and the Strategy of Choices The problem of engagement Conditions of communication and engagement Supportive Authority Re-thinking correctional treatment The strategy of choices Final comments 5. Cognitive Self Change Four Basic Steps Collaboration and the Strategy of Choices Brief Notes on Program Delivery: group size, duration and intensity, facilitator qualifications and training 6. Extended Applications of Supportive Authority Why offenders need help Not Either/Or: some promising examples The system as the intervention: some recent examples Supportive Authority, revisited An idealistic proposal (with modest expectations) 7. How we know: some observations about evidence 1) Introduction 2) Cognitive Self Change 3) The Significance of Subjectivity 4) Science and subjectivity References Index.
Keywords: Self psychology; Self-disclosure.; Forensic psychology; Criminals -- Rehabilitation